Social media analytics using Greenplum's data computing appliance - Schleier-Smith, Johan; Safari eBooks; O'Reilly strata making data work conference (2011 : Santa Clara, CA) ([United States?] : O'Reilly Media, 2011)
"Social media websites are producing ginormous amounts of data and creating a massive demand for insight related to users, how they engage with features, where they are coming from, why they are visiting, what excites them, and so forth." --Resource description page.
Title from title screen.
Recorded at O'Reilly strata making data work conference: Feb. 1-3, 2011, Santa Clara, Calif.
Electronic reproduction.
Keywords: Internet marketing; Social media; Marketing research; Consumer profiling; Electronic books